A Comparative Study of Automated Blood Pressure Device and an Approved Standard Blood Pressure Measuring Device in Young Healthy Population - Jha, Rakesh Kumar; Shrewastwa, Mukesh Kumar; Poudel, Abhishek (Journal of Nepalgunj Medical College, 2025)
Introduction: Blood pressure is a key indicator of cardiovascular health. Automated devices are widely used for convenience, but their accuracy compared with the auscultatory method in young healthy adults remains under investigation.Aims: To determine whether automated and auscultatory blood pressure measurement methods show clinically meaningful differences in a young healthy cohort and whether sex or arm differences influence readings.Methods: A comparative cross-sectional study using purposive sampling was conducted among 80 medical students aged 20–30 years. Although student samples may not represent the general population, they provide controlled and stable baseline physiological conditions for comparative device evaluation. Blood pressure was measured three times per arm using an automated device and a standard auscultatory method under stable room temperature, controlled lighting, and a quiet environment.Results: Systolic blood pressure measured by the auscultatory method was significantly higher than that obtained by the automated device (right arm: mean difference 2.94 mmHg; left arm: 2.50 mmHg). Diastolic blood pressure differences were not statistically significant. Inter-arm differences were minimal. Males had higher systolic BP than females across both arms, while diastolic differences were negligible.Conclusion: Automated devices slightly underestimate systolic blood pressure compared with the auscultatory method in young healthy adults, while diastolic readings are comparable. Automated monitors are suitable for screening and home monitoring, but clinical decisions near systolic thresholds should preferentially rely on validated auscultatory measurements.